Selfish Behavior among Kindergarten Children (Journal Of Educational and Psychological Researches, 2025)
The research is concerned with the problem of selfish behavior among kindergarten children by verifying its objectives in identifying selfish behavior among kindergarten children and the differences between children in terms of gender. The research community included children from public kindergartens in Baghdad city on both the Karkh and Rusafa sides for the academic year 2023-2024. The selfish behavior scale of 30 items with five alternatives, developed by the researcher, was applied to a random sample of 300 male and female children in kindergarten. The results showed that kindergarten children have selfish behavior. There is a significant difference between male and female students concerning selfish behavior in favor of females. Finally, the researcher made several recommendations and suggestions